R & J accessories and decoration / Mohd Hazim Faiz Ambran... [et al.] - Ambran, Mohd Hazim Faiz; Idris, Nur Yuanna Azurianey; Rimus, Clearressia Christtie; Dussip, Zennia; Yussally, Roitah (2015)
The name of our company is R&J accessories and decorations. We provide a services decoration to the customers such as flowers decoration, house stick, basket and other interesting accessories and decoration. We decided to set up a small shop at the Center Point Kota Kinabalu to generate more income for our company. Our business will be located at Center Point at Kota Kinabalu. Our company aim is to save the environment and support the campaign green earth. Our business will operated in Monday to Sunday. Monday to Friday from 8am to 6pm and Saturday to Sunday 9am to 3pm. We only practises one shift operation hour. Our target market would be the society that located near Kota Kinaballu, in accordance with our business nature we aim to help increase our health of nature for the people to live well in the future.